Características físico-químicas de goiabas minimamente processadas e armazenadas sob refrigeração - Oliveira, Roselene Ferreira (2012)
Guava (Psidium guajava, L.) is one of the most important fruit in tropical and subtropical regions due to its very high consumption "fresh" and its high nutritional value. In the Brazilian market, the red guava pulp correspond to at least 75% of consumer preference is a necessary precondition to industrial use in the manufacture of guava paste, guava in syrup, ice cream and concentrated pulp. Minimal processing of fruits aims to provide a product with characteristics similar to fresh and without losing its nutritional qualities. This work aimed to evaluate the physico-chemical properties of slices of guava (Psidium guajava L.) cultivars 'Paluma' subjected to minimal processing, osmotic dehydration, kiln drying and storage under refrigeration 5°C. The experiment was conducted in a completely randomized design with four replicates and the analyzes of pH, soluble solids, titratable acidity, vitamin C, ratio, reducing sugars, total sugars, anthocyanins, humidity, weight loss, color and gray were made in triplicate . The results of the physicochemical characteristics of guavas and ODseco OD treatments showed that there was significant reduction in moisture content and increase in soluble solids content of the samples provide a useful life of 21 days of storage treatment for guavas and OD 24 days of treatment for guavas ODseco. In this study the osmotic dehydration followed by drying was the best storage pre-treatment of the slices of guava, as prolonged the life of the same resulting in more stable product and physico-chemical characteristic similar to fresh samples.